Relationship between the plant, seeds and physiological characteristics in the soybean - Stecca, Jessica Deolinda Leivas; Diel, Maria Inês; Dal’Col Lúcio, Alessandro; Deak, Evandro Ademir; Ferreira, Matheus Martins; Fipke, Glauber Monçon; Brum, Lucas Nascimento; Martin, Thomas Newton (Ciência agronômica, 2025)
ABSTRACT Canonical correlations estimate important relationships between sets of variables, making it easier to manage studies of a large number of characteristics. The aim of this study was to identify the canonical correlations between the seeds, physiological and plant characteristics of soybean, as well as the Pearson linear correlations within each set of characteristics. A randomised block design was used in the field and a completely randomised design in the laboratory, with four and three replications respectively. Canonical groups were defined between the set of plant characteristics (weight and number of nodules, shoot dry weight, number of pods, 1000-grain weight, and grain yield) and the set of seed variables (shoot and root length, plant dry weight, accelerated ageing, electrical conductivity, first count and germination), the set of physiological variables (protein, carotenoid and guaiacol peroxidase content of the grains and leaves) and the plant variables, and the physiological variables and the seeds. Electrical conductivity has a negative correlation with first count and germination. Grain yields are higher when the weight of the plants, the 1000-grain weight, and the number of vegetable parts per plant are greater, while carotenoids are correlated with the chlorophyll levels. Higher levels of protein in the grains and leaves are associated with a higher 1000-grain weight and higher grain yield. The canonical correlation analysis shows that the sets of plant, seed and physiological variables are not independent, and defines the characteristics that should be given priority in the evaluations.